PROSEDUR UJI KEPATUHAN TERHADAP PRINSIP BERSAING ISLAMI PADA INDUSTRI PERBANKAN SYARIAH: SEBUAH PROPOSAL BERDASARKAN TEORI DAN KAJIAN EMPIRIS ORGANISASI INDUSTRI - Idqan Fahmi; Arief Daryanto; Hermanto Siregar; Harianto Harianto (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2012)
An industry in Islamic Economics is required to compete perfectly regardless of its market structure. How to ensure this rule being implemented in reality, however, has been neglected either in literatures or by industry supervisors. This paper is aimed at proposing a systematic procedure to test the industry compliance toward islamic competition rules. The advance of  theory and empirics of New Empirical Industrial Organization is used to formulate the procedure. There are two conditions to satisfy for an industry to have an islamic competition. The first and necessary condition is rejecting the Traditional Hypothesis which is based on collutive bahaviour of dominant banks. The second and sufficient condition is, the perfect competition is driven more by the intention of syariah compliance rather than due to the pressure of contestability.         Keywords: SCP Paradigm, Perfect Competition, Contestable Market, Traditional Hypothesis, New Empirical Industrial Organization, Islamic Competition, Structural Approach, Nonstructural Approach, Panzar and Rosse Model